The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. V. Description of Squamiger elegans gen. et sp. nov. from Central Madagascar - Hlaváč, Peter; Baňař, Petr (Zootaxa, 2016)
Squamiger elegans, gen. and sp. nov., is described based on a series of specimens collected by sifting of leaf-litter in Ambohitantely Special Reserve, Central Madagascar. The genus is a member of the tribe Clavigerini (Pselaphinae: Clavigeritae) and it is placed into the subtribe Clavigerodina.